Um programa de intervenção para o estabelecimento de escolha condicional por identidade ao modelo em um macaco-prego (Cebus apella) - GOULART, Paulo Roney Kilpp (Universidade Federal do Pará, 2011)
The present study aimed to provide an adult male Capuchin-monkey with behavioral prerequisites for consistent performance in conditional identity matching-to-sample (IDMTS) tasks. The subject had problems in performing IDMTS probably due to adventitious development, during previous training of repeated reversals of simple discrimination, of stimulus control topographies incoherent with those needed for accurate performance in these tasks. The subject was presented with a remedial program designed to specifically develop appropriate topography of stimulus selection, and control for the relevant features of IDMTS tasks. The subject showed accurate conditional IDMTS performance with two stimulus sets after exposure to a non-conditional IDMTS procedure, in which there is no conflict in the control exerted by the stimuli serving as comparisons. Novel stimuli were presented in generalization tests, but no evidence of identity matching transfer was found. Explicit IDMTS training was then carried out with those stimuli, beginning with non-conditional IDMTS. When accuracy was again attained in conditional IDMTS, a new stimulus pair was substituted for the old, with no evidence of IDMTS transfer. Results suggest that the remedial program is effective in developing relational control by the sample stimulus. Some conditions for obtaining IDMTS transfer to new stimulus are discussed. (This research was supported by NIH 5 R01 HD39816-03 (CFDA #93.865)